Strategi yang Efektif dalam Pengembangan Produk Bank Muamalat KC Medan Baru - Amelia, Anika; Yanti, Nursantri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In developing a company must have a strategy that is very effective in developing a product that must be done so that the company is always growing rapidly in the world of market competition. Product development for bank Muamalat KC Medan Baru, the business carried out by the company develops existing products or produces new products and takes a strategic approach to achieve success and avoid risks, and presents products that are attractive, competitive and provide convenience in transactions, as well as according with the needs of society and market industry. The purpose of this study is to find out the strategy for product development at Muamalat Kc Medan Baru bank. The method used is descriptive qualitative method. The results of this study indicate that the product marketing concept that Islamic banks need to pay attention to in developing products and services, namely: needs, wants, demands, production, utility, value and satisfaction. Direct product promotion channels for Bank Muamalat KC Medan Baru are by picking up the ball, introducing the Muamalat DIN application, using the Personal Selling model, optimizing Costomer Service, door to door. Keywords: Product Development Strategy, Bank Muamalat Products